Варіації образу вина в українській романтичній поезії - Науменко, Наталія Валентинівна (My University, 2018)
У статті проаналізовано твори української поезії доби романтизму, до образної структури яких входить концепт «вино». Метою роботи було установити місце даного концепту у формуванні жанрових характеристик окремо взятого віршованого твору. До розгляду взято твори як ліричні (елегії, пісні, філософські поезії), так і ліро-епічні (поеми, балади). Виявлено, що образ вина набуває особливих семантичних рис відповідно до жанру – чинник сюжетотворення, зокрема маркер переломного моменту (у ліро-епіці), алегорія розкоші, символ дружби, перемир’я та єднання (у ліриці). The article represents an analysis of Ukrainian poetry of romantic period (the 19th century) with ‘wine’ for the significant image. The relevance of this work is conditioned by the fact that ‘wine poetry,’ as well as image of wine in Ukrainian literature as a whole, has not been the subject of thorough philological research yet. The purpose of this article was to define the place of the above mentioned conceit in formation of the generic characteristics of a separate verse work. The poems to be studied in this article were both lyrical (an elegy, a song, a philosophical poem) and lyro-epic (a long poem, a ballad etc.), written by Amvrosiy Metlyns’ky, Taras Shevchenko, Yuriy Fed’kovych, Yakiv Schoholiv, Mykhailo Staryts’ky, Pavlo Hrabovs’ky, and Mykola Chernyavs’ky. The imagery of the poems analyzed represented ‘wine,’ first of all, as an artistic detail within the chronotopos of the tavern (‘shynok’), which allowed the writers to show the human loneliness among the crowd (one of the prominent motifs in Romantic literature). Another point was the poet’s reproachful attitude to misusing wine (and alcohol in general), turned into a unique rhetorical figure of opposition between drunkenness and sobriety – for instance, in Shevchenko’s ‘Yakby-to ty, Bohdane pyanyi…’ (If only you could, you drunk Bohdan…). Thirdly, it also was Taras Shevchenko who gave the image of wine the actualization in Romantic style as the symbol of religious rite (Cahors, the so-called ‘church’ red wine) and Eucharist, as it was in Ukrainian literature of Kyiv Rus and Baroque periods. Conclusively, the close reading of all the works made possible for the researcher to expose the additional connotations of image of wine regarding the genre matrix – it became the factor of plot development (particularly, the marker of a climax point in the ballad or the long poem), the allegory of luxury (mostly at the end of the 19th century), the symbol of friendship, reconciliation and unity (first of all, in Taras Shevchenko’s poems which were the interpretations of Ancient Rus narrations, including The Song of Igor’s Campaign).
Keywords: кафедра іноземних мов професійного спрямування; українська поезія; вино України; wine of Ukraine; Ukrainian poetry